KONSEP PENDIDIKAN ISLAM DALAM MEMBINA AKHLAK TERHADAP ANAK - Nur Indah Sari (LPPM STAI DARUSSALAM LAMPUNG, 2015)
The concept of Islamic education in fostering the morals of the children had a great influence on a system of Islamic education, so that in formulating the concept of Islamic education takes the basics of the Quran and al-Hadith. Coaching morals of children may be interpreted to foster behavior that can lead to good and evil. Personal generally have elements of both mind and body are mutually reinforcing unity between one another and can not be liberated and is a human child or a person of immature, gift and a deposit which must be maintained as well as the mandate for the adults, especially the elderly where parents also have a responsibility to the children in many ways, good maintenance, education, development and future.The purpose of this study was to determine the basis and purpose of fostering the morals of children and to determine the method in fostering the morals of children. Based on these results, the authors conclude that the concept of Islamic education is an important foundation in mebina morals of children, where the concept of Islamic education there is a strong foundation namely the Quran and Al-Hadith which will print the child becomes human being virtuous and praiseworthy morals. Factors that play a role in influencing the formation and moral development of children include internal factors and external factors, including heredity, age, personality, and psychological condition of a person and of the environment in which one lives. Generally, the neighborhood is divided into three, namely: family, institution, community